ANALISIS EFISIENSI BOILER UNIT 2 DAN 4 DI PT. PLN (PERSERO) WIL. KALSELTENG SEKTOR PLTU ASAM-ASAM - Aries Aditya Kurniawan; Aqli Mursadin (Scientific Journal of Mechanical Engineering Kinematika, 2019)
Boiler is a tool used to produce steam / steam for various purposes. The water in the boiler is heated by heat from the fuel combustion (other heat source) resulting in heat transfer from the heat source to the water causing the water to become hot or transformed into steam. Direct Methods Also known as "input-output method" because this method requires only output / output (steam) and heat input / fuel (fuel) for efficiency evaluation. From the results of boiler efficiency study from August 8, 2017 to August 17, 2017 with a total average - unit 4 has a boiler efficiency 75.5012% higher than unit 2 which only amounted to 65.24% 84%. The high efficiency of boiler unit 2 is due to the average pressure on unit 4 of 86.9229 bar is greater than the pressure of unit 2 which is only about 82.9155 bar. Then Main steam flow on unit 4 is 66,6605 kg / s while unit 2 is only 63,61111 kg/s. For feed water flow unit 4 only able to flow 65,9 kg / s and unit 2 equal to 66,675 kg/s.